ICASSP 2021 - 2021 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2021
DOI: 10.1109/icassp39728.2021.9413638
|View full text |Cite
|
Sign up to set email alerts
|

Towards Explaining Expressive Qualities in Piano Recordings: Transfer of Explanatory Features Via Acoustic Domain Adaptation

Abstract: Emotion and expressivity in music have been topics of considerable interest in the field of music information retrieval. In recent years, mid-level perceptual features have been suggested as means to explain computational predictions of musical emotion. We find that the diversity of musical styles and genres in the available dataset for learning these features is not sufficient for models to generalise well to specialised acoustic domains such as solo piano music. In this work, we show that by utilising unsupe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Researchers increasingly apply machine learning techniques to clarify relationships between music's structural features (from low-level acoustic features to mid-level perceptual ones) and participants’ perceptual responses (Chowdhury & Widmer, 2021; Cowen et al, 2020; Zhukov, 2007). Estimating the importance of analyzed features can help researchers identify which ones to assess in perceptual experiments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers increasingly apply machine learning techniques to clarify relationships between music's structural features (from low-level acoustic features to mid-level perceptual ones) and participants’ perceptual responses (Chowdhury & Widmer, 2021; Cowen et al, 2020; Zhukov, 2007). Estimating the importance of analyzed features can help researchers identify which ones to assess in perceptual experiments.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed a data set containing the number of distinct note attacks, pitch height, and nominal mode (as defined by the composer) from the first eight measures (appending pick-up measures where applicable) of each prelude in Bach's The Well-Tempered Clavier and Chopin's Preludes . Previous studies in empirical musicology (Poon & Schutz, 2015) and music psychology (e.g., Anderson & Schutz, 2022; Battcock & Schutz, 2022; Chowdhury & Widmer, 2021) have analyzed these corpora, providing an opportunity for exploring the broader musicological and perceptual implications of these analyses. Here, we limited our selection to eight-measure excerpts (appending pick-up measures where applicable) for methodological consistency with parallel work involving perceptual experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We learn these features from the Mid-level Dataset [15] using a receptive-field regularised residual neural network (RF-ResNet) model [17]. Since we intend to use this model to extract features from solo piano recordings (a genre that is not covered by the original training data), we use a domainadaptive training approach as described in [18]. We use an input audio length of 30 seconds, padded or cropped as required.…”
Section: Mid-level Featuresmentioning
confidence: 99%
“…In particular, we focus on so-called Mid-level Perceptual Features -relatively high-level musical qualities that are considered to be perceptually important [5]; in our work, these are learnt from human annotations. Previous research has shown these features to have the capacity to predict musical emotions as well as to disentangle different performances based on emotion [7][8][9].…”
Section: Introductionmentioning
confidence: 99%